Sleep of the guiltless. - Loh, Xiu Hui. (2009)
“Sleep of the Guiltless” is a 24 minute short film produced by the student group, Wreck Focus Productions, for the completion of their Final Year Project. Wreck Focus Productions comprises of Loh Xiu Hui, Meredith Woo, Tan Hui Hua and Andrea Ng, all of whom are final-year undergraduates at the Wee Kim Wee School of Communication and Information, Nanyang Technological University. The project is supervised by Mr James Mairata. The aim of this report is to describe and chronicle the film-making process of “Sleep of the Guiltless”. We hope to offer a glimpse of the important stages of our film-making process by providing candid, behind-the-scenes information, which audiences seldom see. Detailing the core ideas and themes of the movie, we also hope to provide a better understanding of the film for the viewer.